The political communication process among Chinese moslem society - Hidayati, Ulfah (Informasi, 2019)
This study aimed to find out the political communication process occurring among the electorates in making decision of electing. In detail the source of information is known to be used for concerning the Pilgub DKI Jakarta of 2012, type of information obtained, and electing decision making among the Chinese Moslem community of Masjid Lautze Jakarta. Output of research was knowledge about the political communication process occurring until the electing decision making.This research referred to the conception that communication is a process of delivering message to exert effect (in this case the electing decision). The mass media effect theory was used as one of references in this research because the mass media pertained directly to the communicant in political communication process. The method used was qualitative one using in-depth interview technique for collecting data with 14 informants from the Chinese Moslem community of Masjid Lautze Jakarta. From the research it could be found that the dominant information source used to access the political information was mass media (television and newspaper), BBM (Black Berry Messenger), interpersonal communication media, group communication media, and other information source such as outdoor advertisement. Meanwhile in the term of information type, the information on Jokowi-Ahok couple became the most widely obtained one by the members of society. The electing decision was generally affected by such factors as mass media, interpersonal communication, group communication, organization, and observing Jakarta’s condition directly. The opinion leader factor (ustadz and foundation leader) did not have influence in this research.Penelitian ini betujuan untuk mengetahui proses komunikasi politik yang berlangsung pada khalayak pemilih dalam pengambilan keputusan memilih. Secara detailnya diketahui sumber informasi yang digunakan untuk mendapatkan informasi mengenai Pilgub DKI Jakarta 2012, jenis informasi yang didapatkan, dan pengambilan keputusan memilih di kalangan warga muslim Tionghoa jama’ah Masjid Lautze Jakarta. Output dari penelitian ini adalah pengetahuan mengenai proses komunikasi politik yang berlangsung hingga samapai pada tahap pengambilan keputusan memilih. Penelitian ini mengacu pada pemahaman bahwa komunikasi adalah suatu proses penyampaian pesan yang akan menghasilkan efek (dalam hal ini keputusan memilih). Teori mengenai efek media massa digunakan sebagai salah satu acuan dalam penelitian ini karena media massa langsung bersinggungan dengan komunikan dalam proses komunikasi politik. Metode yang digunakan adalah kualitatif dengan teknik pengumpulan data menggunakan in-depth interview pada 14 narasumber warga muslim Tionghoa Jama’ah Masjid Lautze Jakarta. Dari penelitian tersebut didapatkan sumber informasi dominan yang digunakan untuk mengakses informasi politik adalah media massa (televisi dan koran), BBM (Black Berry Massanger), media komunikasi interpersonal, media komunikasi kelompok, dan sumber informasi lainnya seperti iklan luar ruangan. Sedangkan untuk jenis informasi maka informasi mengenai pasangan Jokowi Ahok menjadi informasi yang paling banyak didapatkan oleh warga. Untuk keputusan memilih secara umum dipengaruhi oleh beragam faktor yaitu oleh media massa, komunikasi interpersonal, komunikasi kelompok/organisasi, dan melihat kondisi Jakarta secara langsung. Untuk faktor opinion leader (ustad dan pimpinan yayasan) justeru tidak berpengaruh dalam penelitian ini.